Interplay between energy metabolism and NADPH oxidase-mediated pathophysiology in cardiovascular diseases - Jie, Haipeng; Zhang, Jingjing; Wu, Shuzhen; Yu, Luyao; Li, Shengnan; Dong, Bo; Yan, Feng (Frontiers in Pharmacology, 2025)
Sustained production of reactive oxygen species (ROS) and an imbalance in the antioxidant system have been implicated in the development of cardiovascular diseases (CVD), especially when combined with diabetes, hypercholesterolemia, and other metabolic disorders. Among them, NADPH oxidases (NOX), including NOX1-5, are major sources of ROS that mediate redox signaling in both physiological and pathological processes, including fibrosis, hypertrophy, and remodeling. Recent studies have demonstrated that mitochondria produce more proteins and energy in response to adverse stress, corresponding with an increase in superoxide radical anions. Novel NOX4-mediated modulatory mechanisms are considered crucial for maintaining energy metabolism homeostasis during pathological states. In this review, we integrate the latest data to elaborate on the interactions between oxidative stress and energy metabolism in various CVD, aiming to elucidate the higher incidence of CVD in individuals with metabolic disorders. Furthermore, the correlations between NOX and ferroptosis, based on energy metabolism, are preliminarily discussed. Further discoveries of these mechanisms might promote the development of novel therapeutic drugs targeting NOX and their crosstalk with energy metabolism, potentially offering efficient management strategies for CVD.